Pengaruh Tinggi Pangkasan Batang Utama dan Jumlah Cabang Primer yang Dipelihara terhadap Produksi Minyak Jarak Pagar (Jatropha curcas L.) - Ince Raden; Bambang S. Purwoko; , Hariyadi; Munif Ghulamahdi; Edi Santosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The objective of this research was to study shoot architecture in relation to growth, increase production and seed oil content through various stem pruning and number of primary branches. This research was conducted using Randomized Complete Block Design with single factor. It consisted of ten treatments, i.e., K=kontrol, T20= height of stem pruning at 20 cm from soil and without control on number of primary branches, T20-2=height of stem pruning at 20 cm from soil and two primary branches, T20-3= height of stem pruning at 20 cm and three primary branches, T30= height of stem pruning at 30 cm and without control on number of primary branches, T30-2= height of stem pruning at 30 cm and two primary branches, T30-3=height of stem pruning 30 cm and three primary branches, T40=height of stem pruning at 40 cm and without control on number of  primary branches, T40-2=height of stem pruning at 40 cm and two primary branches, and T40-3=height of stem pruning 40 cm and three primary branches. The results showed that stem pruning increased number of primary branches. The highest seed oil content and seed production was achieved T40 and T30-3 treatments i.e., 323.81 g/plant or 0.810 ton/ha and 320.61 g/plant or 0.802 ton/ha with seed oil yield 244.56 kg/ha and 276.61 kg/ha, respectively.   Key words : Jatropha curcas L., seed oil content, pruning, primary branches